Development of Lean Assessment Tool for Healthcare Industry - Dodgalih Nur Muhammad; Putu Dana Karningsih (Institut Teknologi Sepuluh Nopember, 2020)
The concept of lean is originated in manufacturing industry. However, this concept also has been widely adopted in service industry, from airlines to retailers. There are several healthcares or hospitals in various countries that has implemented Lean. The hospital that has adopted lean, shown various improvements, such as increase on efficiency and flexibility, reduction cost and infections cases. It is important to have lean assessment to measure leanness level after implementing lean. Lean Assessment Tool is utilized to measure effectiveness and efficiency of lean implementation in a particular company. There are many studies on Lean Assessment Tool for manufacturing and service industry in general. However, Lean Assessment Tool that is specific for hospital is not yet available. Therefore this study aims to develop a Lean Assessment Tool (LAT) for healthcare. First, quantitative and qualitative dimensions and indicators are gathered from literature study. Proposed dimensions and indicators are then selected and validated using the Fuzzy Delphi method. There are seven quantitative dimensions, which are quality, time, internal transportation, employee involvement, cost, customer, and inventory. While, there are six qualitative dimensions, which are quality, process, employee involvement, vertical information system, technology upgrading, and management commitment. Measurement method by using fuzzy logic to calculate leanness level for both quantitative and qualitative indicator is then applied. Leanness level will be mapped using radar plots.